Effects of Heated Pneumoperitoneum on Inflammation, Oxidative Stress, and Peritoneal Histology in Female Dogs That Underwent Video-Assisted Ovariohysterectomy - Vanessa Milech; Juliana S. de Oliveira; Michelli A. W. de Ataide; Gabriela P. Coradini; Thaís R. Mann; Vanessa Z. Sarturi; Hellen F. Hartmann; Marcella T. Linhares; Bernardo N. Antunes; Cínthia M. de Andrade; Glaucia D. Kommers; Marco A. M. Silva; et al. (Veterinary Medicine International)
Laparoscopic procedures require the creation of pneumoperitoneum. CO2, which must be cold and dry, is the standard gas used in such surgeries. The type of gas used, its temperature, and moisture may change the peritoneal surface and cause systemic and local oxidative stress. Our objective is to evaluate the influence of pneumoperitoneum heating on the occurrence of histological lesions in the peritoneum, inflammation, plasma oxidative stress, and on the mesothelial surface in patients undergoing video-assisted ovariohysterectomy. Twenty canine females were included and distributed evenly into two groups: heated CO2 (HG) and unheated CO2 (UHG). The biomarkers of inflammation and oxidative stress were evaluated before insufflation (T0), at 30 min (T1), and at 60 min (T2) of exposure to CO2. Biopsies of the peritoneal tissue for histological evaluation were performed at T0 and T2. Regarding plasma parameters, acetylcholinesterase (AChE) showed a greater activity in the HG at T1 (p=0.0268) and T2 (p=0.0423); in turn, butyrylcholinesterase (BChE) showed a greater activity at T2 in the HG (p=0.0175) compared with T0. Catalase activity (CAT) was different between HG times; it was higher at T1 (p=0.0253). There was a decrease in the levels of substances reactive to thiobarbituric acid (TBARS) (p=0.0117) and in glutathione (GSH) (p=0.0114) between T0 and T2 in the UHG. Regarding tissue oxidative stress, the CAT in the HG showed a greater activity at T2 than T1 (p=0.0150). By comparing the groups at each time, there was a difference only at T2 (p=0.0288), being greater in the HG. Regarding the activity of superoxide dismutase (SOD) in the HG, there was a difference between T2 in relation to T0 and T1 (p=0.0181); finally, there was an increase only at T1 (p=0.0287) in the UHG when comparing groups at the same time. There were no differences in the histological parameters evaluated. Our study demonstrates that the heating of CO2 generates a greater inflammatory response and forms reactive oxygen species (ROS) at the plasma and peritoneal levels.